DAMPAK PROGRAM BANTUAN LANGSUNG TUNAI TERHADAP KETANGGUHAN MASYARAKAT MENJALANI KETENTUAN PENANGANAN WABAH COVID-19 STUDI DI DESA LOKORY KECAMATAN TANARIGHU KABUPATEN SUMBA BARAT - Chevin Nara Haba (JPASDEV : Journal of Public Administration and Sociology of Development, 2022)
The Covid-19 pandemic has not only had an impact on health, but also on social and economic conditions. Policies for handling the COVID-19 pandemic through PSSB to PPKM have caused a decline in community economic activity. Government policies limit their activities in the following ways: workers are laid off or even laid off, farmers cannot sell their produce due to a shortage of buyers, transport drivers no longer have passengers, and so on. Conditions like this can lead to social instability, income inequality, and regional disparities. Therefore, to avoid some of these things, the government revised the regulation. One of the revised regulations is Permendagri Number 69 of 2018. The purpose of this research is to examine the impact of the BLT program on community resilience in carrying out the provisions for handling the COVID-19 outbreak in Lokory Village, Tanarighu District, West Sumba Regency. The research method used is a qualitative research method which is often referred to as a naturalistic research method because the research is carried out to examine a natural place (natural setting). And in this study, the results of the government's collaboration in facing the realization of a resilient community facing the COVID-19 pandemic in Lokory Village, Tanarighu District, West Sumba Regency through the Government Cooperation scheme, with direct cash assistance there are still people whose needs have not been met, meaning that they are not strong, then the form of government cooperation namely by involving bringing new innovations in the form of selling businesses online so that every community who sells their wares can be online and can be delivered directly to the buyer's place and comply with health protocols and with the marketplace application we can connect sellers with buyers. The supporting factor is the government's transparency to the public. supporters of the village government have always been transparent with us as the village government, the obstacles that occur in the BLT Program Against Community Resilience In Lokory, Tanarighu District, West Sumba Regency, so far no action has been taken. at all regarding the resolution of obstacles that occur Efforts to create a community that is resilient to the COVID-19 pandemic in Lokory Village seen from the principle of good governance, namely the level of community participation is very high, and is carried out in accordance with the Decree of the Minister of Social Affairs of the Republic of Indonesia Number 54/Huk/2020 concerning the Implementation of Aid Social Food and Cash Social Assistance in Handling the Impact of Corona Virus Disease 2019 (Covid-19), and in Services, the government is transparent and transparent to the publicKeywords: program implementation, community resilience, COVID 19